Stakeholders’ involvement in the process of city branding – Theory versus practice - Glińska, Ewa (Journal of Public Governance, 2017)
In connection with the development of the relational paradigm in marketing of public organizations, as well as in territorial branding, it is increasingly emphasized that involvement of local stakeholders in the process of formulating and implementing the city brand concept is a key condition for the success of such projects. The aim of the paper is to determine whether a more participatory approach in forming the desired image of cities, taking into account the opinions of various groups of local stakeholders, allows municipalities in Poland to define a clearer concept of city brand. The study uses statistical analysis of the results of a survey carried out among heads of promotion departments of 217 municipalities. The results show the presence of a statistically significant correlation between the number of stakeholders and ordinary citizens (as one of the local interest groups) involved in the process associated with the formation of the desired image of the city, and the level of clarity the local governments have regarding the definition of the concept.